New Approaches to Macroeconomic Stability - V.M. Postolaty (Problems of the Regional Energetics)
The structure of the economy of the Republic of Moldova was reviewed and the analysis of the main macroeconomic indicators, including the energy sector, was conducted. For a long period, data on the state of Moldova’s energy, technical and economic indicators and development trends have been analyzed. Particular attention is paid to the definition of changes in the value of the real gross domestic product (GDP), taking into account the coefficient of deflation. The quantitative dependence of GDP on the volumes of "Output" and "Intermediate Consumption" is shown. It is revealed that the more “Intermediate Consumption”, the lower the GDP, ceteris paribus. The major share of the cost of the industry sector is covered by “Intermediate Consumption”, which in turn is higher, the higher the tariffs for energy, materials and other services provided by the industries to each other. It was concluded that tariff growth should not overtake real GDP growth over the past few years. The results of the calculations and their analysis show that, in reality, the growth of tariffs is far ahead of the growth of real GDP, which does not contribute to the stable development of the country's economy. It was proposed to revise tariffs, in particular for energy resources, and to bring the rates of their change in line with the growth rates of real GDP. An approach has been formulated for determining the marginal levels of tariffs, based on the condition that their growth rates do not exceed the growth rates of real GDP.